2007
DOI: 10.1248/jhs.53.92
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Carboxylesterase Metabolites of Residual Malathion in Wheat Kernels Using Semi-Micro Radio Liquid Chromatography

Abstract: Since residual malathion in wheat kernels is shown to be enzymatically decomposed during sample preparation using the Japanese official method for pesticide analysis, the decomposition products were identified by semi-micro radio liquid chromatography (LC). The reaction mixture of the supernatant of wheat kernel homogenate incubated with [14 C] malathion for 0-8 hr was fractionated, and the radioactive decomposition products in the fractions were identified by comparison with the retention time of fifteen refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…11) However, it could not be elucidated whether this MMC was MMCα, MMCβ or a mixture of the two. The aim of this paper is to characterize wheat kernel CE by identification of the MMC isomers formed from malathion and to investigate the degradability of malathion and each product by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11) However, it could not be elucidated whether this MMC was MMCα, MMCβ or a mixture of the two. The aim of this paper is to characterize wheat kernel CE by identification of the MMC isomers formed from malathion and to investigate the degradability of malathion and each product by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Dibutyl amine acetate as ion pair reagent for liquid chromatography (LC) was from Tokyo Kasei Kogyo Co., Ltd. (Tokyo, Japan). MDC, desmethyl malathion (DMal), and desmethyl malathion dicarboxylic acid, which were synthesized in our previous study, 11) and MMCα and MMCβ, which were newly synthesized, were used as standard reference materials of malathion metabolites. Chemical Synthesis --MMCα: MMCα was synthesized enzymatically as follows; Malathion (2 g) was added to porcine pancreatic lipase solution (20 g/150 ml) in 0.02 M sodium phosphate buffer (pH 7.0) and incubated at 36 • C for 40 hr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The products also suggested that the degradation was due to CE. 9,10) CE hydrolyzes carboxylesters and belongs to the esterase family. 11) 1-Naphthyl acetate and pnitrophenyl acetate are generally recognized as typical substrates of CE.…”
Section: Introductionmentioning
confidence: 99%